Streamlined targeting of Amaryllidaceae alkaloids from the bulbs of Crinum scillifolium using spectrometric and taxonomically-informed scoring metabolite annotations. (November 2020) - N'Tamon, Amon Diane; Okpekon, Aboua Timothée; Bony, Nicaise F.; Bernadat, Guillaume; Gallard, Jean-François; Kouamé, Tapé; Séon-Méniel, Blandine; Leblanc, Karine; Rharrabti, Somia; Mouray, Elisabeth; Grellier, Philippe; Ake, Michèle; et al.
Abstract: Four undescribed alkaloids have been isolated from the bulbs of the previously unstudied Crinum scillifolium . These compounds were targeted following a state-of-the-art molecular networking strategy comprising a dereplication against in silico databases and re-ranking of the candidate structures based on taxonomically informed scoring. The unreported structures span across a variety of Amaryllidaceae alkaloids appendages. Their structures were unambiguously elucidated by thorough interpretation of their HRESIMS and 1D and 2D NMR data, and comparison to literature data. DFT-NMR calculations were performed to support the determined relative configurations of scillitazettine and scilli- N -desmethylpretazettine and their absolute configurations were mitigated by comparison between experimental and theoretically calculated ECD spectra. The lack of a methyl group on the nitrogen atom in the structure of scilli- N -desmethylpretazettine series is highly unusual in the pretazettine/tazettine series but the most original structural feature in it lies in its 11 α disposed hydrogen, which is new to pretazettines. The antiplasmodial as well as the cytotoxic activities against the human colon cancer cell line HCT116 were evaluated, revealing mild to null activities. Graphical abstract: Image 1 Highlights: Four undescribed Amaryllidaceae alkaloids were isolated from Crinum scillifolium . These structures were pinpointed by a Molecular Networking strategy (MN). The MN was tagged by dereplication vs in silico data base and taxonomical reranking Structures were determined by extensive spectroscopic analyses. Compounds were evaluated for their antiplasmodial and cytotoxic activities.